2013
DOI: 10.1128/mcb.01149-12
|View full text |Cite
|
Sign up to set email alerts
|

TRIP6 Regulates p27KIP1 To Promote Tumorigenesis

Abstract: TRIP6 is an adaptor protein that regulates cell motility and antiapoptotic signaling. Although it has been implicated in tumorigenesis, the underlying mechanism remains largely unknown. Here we provide evidence that TRIP6 promotes tumorigenesis by serving as a bridge to promote the recruitment of p27 KIP1 to AKT in the cytosol. TRIP6 regulates the membrane translocation and activation of AKT and facilitates AKT-mediated recognition and phosphorylation of p27 KIP1 specifically at T157, thereby promoting the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Previous study reported that TRIP6 can bind to p27 Kip1 and promote its phosphorylation at T157, leading to cytosolic mislocalization [10]. In this report, we showed that adhesion to FN decreased TRIP6 expression, thereby increasing nuclear p27 Kip1 expression via decreasing phosphorylation of p27 Kip1 at T157.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Previous study reported that TRIP6 can bind to p27 Kip1 and promote its phosphorylation at T157, leading to cytosolic mislocalization [10]. In this report, we showed that adhesion to FN decreased TRIP6 expression, thereby increasing nuclear p27 Kip1 expression via decreasing phosphorylation of p27 Kip1 at T157.…”
Section: Discussionmentioning
confidence: 52%
“…Previous study demonstrated that knockdown of TRIP6 in glioblastoma or ovarian cancer can elevate nuclear p27 Kip1 expression [10]. As we know, adhesion of tumor cells to FN can induce cell cycle arrest and protect tumor cells from chemotherapeutic drug-induced apoptosis via increasing nuclear p27 Kip1 protein expression [5,6].…”
Section: Trip6 Knockdown Upregulates Nuclear P27 Kip1 Expressionmentioning
confidence: 98%
See 1 more Smart Citation
“…TRIP6 can also regulate prosurvival signaling via activation of NF-kB, extracellular signal-regulated kinase (ERK), and phosphatidylinositol 3-kinase (PI3K)/AKT, and nuclear TRIP6 acts as a transcriptional coregulator of AP-1 and NF-kB. These data suggest that TRIP6 functions at a point of convergence of multiple signaling pathways critical for cancer development (29). Thus, TRIP6 acts as an oncogene that partially accounts for the autonomous migratory, invasive, and proliferative properties of Ewing sarcoma cells independent of EWS/FLI1.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, in nasopharyngeal cancer cells (NPC), TRIP6 overexpression/knockdown results in significant enhancement/inhibition of NPC cell migration, respectively (31). Finally, knockdown of TRIP6 in glioblastoma or ovarian cancer xenografts restores nuclear p27 (KIP1) expression and impairs tumor proliferation and may have a significant impact on enhanced NF-kB activity, resistance to apoptosis, and Fas-mediated cell invasion in glioblastomas (29,32). Paradoxically, in desmoid tumors, TRIP 6 was overexpressed in the good outcome group.…”
Section: Discussionmentioning
confidence: 99%